BPBD Strategy in Landslide Disaster Management: A Case Study of Sijunjung Regency - Iskandar, Mhd. Fadhel Adli; Alhadi, Zikri (The Future of Education Journal, 2025)
This study aims to analyze the strategy of the Regional Disaster Management Agency (BPBD) of Sijunjung Regency in handling landslide disasters. Sijunjung Regency experienced 34 landslide events in 2024, ranking third highest in West Sumatra. This research employs a descriptive qualitative method with the Kooten strategy theory approach, which includes four main dimensions: organizational strategy, program strategy, resource support strategy, and institutional strategy. Data were collected through in-depth interviews with BPBD officials, sub-district heads, village chiefs, and disaster experts, supplemented by documentation and field observations. The results indicate that BPBD of Sijunjung Regency has implemented organizational strategy through cross-sector coordination and disaster awareness campaigns. Program strategy is reflected in mitigation efforts, emergency response, and infrastructure recovery, while resource support strategy involves the utilization of human resources, equipment, and available budget. Institutional strategy is evident in the use of regulations, SOPs, and the delegation of authority in disaster management. However, the implementation of these strategies still faces challenges, including limited budgets, low community participation, and communication barriers in affected areas. Overall, the BPBD strategy in Sijunjung Regency has been relatively effective, but it requires strengthening in funding, collaboration, and community empowerment to ensure that landslide disaster management is more efficient, sustainable, and comprehensive.